Tunable single-phase magnetic behavior in chemically synthesized AFeO3–MFe2O4 (A = Bi or La, M = Co or Ni) nanocomposites. Issue 48 (30th November 2018) - Sarkar, T.; Muscas, G.; Barucca, G.; Locardi, F.; Varvaro, G.; Peddis, D.; Mathieu, R.
Abstract : Tailoring the magnetic properties of nanocomposites consisting of correlated electron oxide systems via a novel synthesis technique. Abstract : The properties of magnetic nanocomposites rely strongly on the interplay between those of the constituent components. When the individual components themselves are complex systems belonging to the family of correlated electron oxide systems which typically exhibit exotic physical properties, it becomes nontrivial to customize the properties of the nanocomposite. In this paper, we demonstrate an easy, but effective method to synthesize and tune the magnetic properties of nanocomposites consisting of correlated electron oxide systems as the individual components. Our method is based on a novel synthesis technique by which the two components of the nanocomposite can be directly integrated with each other, yielding homogeneous samples on the nanoscale with magnetic behavior reminiscent of a single phase. We illustrate our method using multiferroic BiFeO3 (BFO) and LaFeO3 (LFO) as the major phase ( i.e., matrix), and MFe2 O4 (M = Co 2+ or Ni 2+ ) as the embedded magnetic phase. Furthermore, we show that by a proper selection of the second phase in the nanocomposite, it is possible to customize the magnetic properties of the matrix. We illustrate this by choosing CoFe2 O4 and NiFe2 O4, two oxides with widely differing magnetic anisotropies, as the embedded phase, and demonstrate that the coercivity of BFO and LFO can be increased or decreased depending on the choice of the embedded phase in the nanocomposite.